'A Lady on the Street but a Freak in the Bed': On the Distinction Between Erotic Art and Pornography. (18th December 2018) - Eaton, A W
Abstract: How, if at all, are we to distinguish between the works that we call 'art' and those that we call 'pornography'? This question gets a grip because from classical Greek vases and the frescoes of Pompeii to Renaissance mythological painting and sculpture to Modernist prints, the European artistic tradition is chock-full of art that looks a lot like pornography. In this paper I propose a way of thinking about the distinction that is grounded in art historical considerations regarding the function of erotic images in 16 th -century Italy. This exploration suggests that the root of the erotic art/pornography distinction was—at least in this context—class: in particular, the need for a special category of unsanctioned illicit images arose at the very time when print culture was beginning to threaten elite privilege. What made an erotic representation exceed the boundaries of acceptability, I suggest, was not its extreme libidinosity but, rather, its widespread availability and, thereby, its threat to one of the mechanisms of sustaining class privilege.